Socio-rhetorical reading of the remembrance meal in Luke 22:19-27 in the context of the church in Africa - Godwin A. Etukumana; Ezele J. Areghan (Nsukka Journal of Religion and Cultural Studies, 2023)
Religious texts are seen by their faithful readers as having the ability to connect them with the sacred. These texts are for the illumination and transformation of the community. The relationship between the divine and human within a written text is crucial for religious understanding. For this reason, this paper will focus on the sacred texture of Luke 22:14–27 to clarify the meaning of the Lukan remembrance meal in its context and the context of the church and humanity today. In socio-rhetorical hermeneutics, the sacred texture is important when it expresses the relevance of the text to its community. It implores the reader to be interested in the way the text deals with God and religious life. A Biblical text mediates words about God. It activates and prescribes a specific view of the deity to the audience. Exploring the sacred text enables the reader to perceive the written text as the word of God intended for teaching and educating the faith community, and at the same time, it provides a norm for the community. This paper will use socio-rhetorical interpretation to examine the text of Luke 22:19–27 within the context of the Church in Africa as revealed in the text. The Lukan Jesus expects the Church in Africa to perform its duties in its immediate context. This paper envisages that a text has a transforming and illuminating ability for the faith community (the church) in Africa.